Melanoma Vaccines: Comparing Novel Adjuvant Treatments in High-Risk Patients - Joseph C. Broderick; Alexandra M. Adams; Elizabeth L. Barbera; Spencer Van Decar; Guy T. Clifton; George E. Peoples (Vaccines)
Background: The emergence of checkpoint inhibitors (CPIs) has significantly improved survival outcomes in later-stage melanoma. However, the efficacy of these treatments remains limited, with around 50% of later-stage melanoma patients experiencing recurrence. As variable response rates to CPIs persist, the development of cancer vaccines has emerged as a potential strategy to augment antitumor immune responses. Results: This review compares two promising personalized therapeutic cancer vaccine trials in advanced melanoma: Elios Therapeutics’ Tumor Lysate (TL) vaccine and Moderna’s mRNA-4157 vaccine. The TL vaccine, which utilizes yeast cell wall particles (YCWPs) loaded with autologous tumor lysate, and the mRNA-4157 vaccine, which encodes up to 34 patient-specific neoantigens, both aim to stimulate robust tumor-specific immune responses. Both trials were phase 2b randomized studies, with Elios Therapeutics’ trial employing a double-blind, placebo-controlled design, while Moderna’s was open-label. Both trials had roughly equivalent sample sizes (n = 187 and n = 157, respectively) with similar demographics and disease characteristics. The TL trial reported improvements in disease-free survival (DFS) with a hazard ratio (HR) of 0.52 (p < 0.01) over 36 months, whereas the mRNA-4157 trial demonstrated improvements in recurrence-free survival (RFS) with an HR of 0.56 (p = 0.053) over 18 months. The TL vaccine exhibited lower rates of related grade 3 adverse events (<1%) compared to the mRNA vaccine (12%). Key differences between the two trials include the use of CPIs, with 100% of patients in the mRNA trial receiving pembrolizumab versus 37% of the patients in the TL trial receiving either an anti-PD-1 or anti-CTLA-4. The production processes also varied significantly, with the mRNA vaccine requiring individualized sequencing and a 9-week production time, while the TL vaccine utilized tumor lysate with a 1–3-day production time. Conclusions: While both vaccines demonstrated promising efficacy, future phase 3 trials are needed to further evaluate their potential as adjuvant therapies for melanoma. This review highlights the comparative strengths and limitations of these vaccine platforms, providing insight into the evolving landscape of adjuvant cancer vaccines.